Position/torque hybrid control of a rigid, high-gear ratio quadruped robot. (17th September 2018) - Sim, Okkee; Jung, Taejin; Lee, Kang Kyu; Oh, Jaesung; Oh, Jun-Ho
ABSTRACT: In this study, we introduce position/torque hybrid control for a newly designed rigid and high-gear ratio quadruped robot. The Experimental results indicated that the use of this control strategy allows the quadruped robot to maintain its stability while walking, and foot contact can be stabilized with only knee torque control and other joints are position controlled, without contact force feedback. Additionally, we suggested a smooth pattern connection method within or from preview control to the center of mass natural dynamics, and vice versa. We validated the proposed control strategies by conducting experiments. GRAPHICAL ABSTRACT: